2010
DOI: 10.1523/jneurosci.4634-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Receptor Endocytosis Prevents Adaptations in Ventral Tegmental Area GABA Transmission Induced during Naloxone-Precipitated Morphine Withdrawal

Abstract: Chronic morphine drives adaptations in synaptic transmission thought to underlie opiate dependence. Here we examine the role of -opioid receptor (MOR) trafficking in one of these adaptations, specifically, changes in GABA transmission in the ventral tegmental area (VTA). To address this question, we used a knock-in mouse, RMOR (for recycling MOR), in which genetic change in the MOR promotes morphine-induced receptor desensitization and endocytosis in GABA interneurons of the VTA. In wild-type mice (postnatal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 33 publications
2
59
0
Order By: Relevance
“…A characteristic feature of morphine withdrawal is an increase in GABAergic activity in regions like the VTA (Bagley et al, 2011), leading to enhanced GABAergic neurotransmission onto VTA dopamine neurons (Bonci and Williams, 1997;Madhavan et al, 2010a), associated with detrimental opiate withdrawal symptoms (Madhavan et al, 2010a). Accordingly, we observed that withdrawal from chronic morphine pretreatment (n ϭ 15) increased the frequency of mIPSCs onto VTA dopamine neurons by 66.08% (F (1,48) ϭ 4.09, p Ͻ 0.05, one-way ANOVA; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A characteristic feature of morphine withdrawal is an increase in GABAergic activity in regions like the VTA (Bagley et al, 2011), leading to enhanced GABAergic neurotransmission onto VTA dopamine neurons (Bonci and Williams, 1997;Madhavan et al, 2010a), associated with detrimental opiate withdrawal symptoms (Madhavan et al, 2010a). Accordingly, we observed that withdrawal from chronic morphine pretreatment (n ϭ 15) increased the frequency of mIPSCs onto VTA dopamine neurons by 66.08% (F (1,48) ϭ 4.09, p Ͻ 0.05, one-way ANOVA; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Reduced dopamine signaling during morphine withdrawal can arise due to increased GABAergic signaling onto VTA dopamine neurons (Bagley et al, 2011). This enhancement of inhibitory signals has been reported to occur as a consequence of morphine withdrawal-induced elevations in cAMP (cAMP superactivation) in GABAergic terminals (Bonci and Williams, 1997;Madhavan et al, 2010a). Together, these findings point to an important role of GABAergic signaling onto VTA dopamine neurons in the occurrence of opiate withdrawal symptoms.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The application of forskolin increases GABA IPSCs in morphine-treated brain slices while dideoxyforskolin, which does not have an effect on AC, did not increase GABA IPSC. 136,137 …”
Section: Molecular Changes In the Ventral Tegmental Areamentioning
confidence: 99%
“…TTX is a highly selective voltagegated sodium channel (VGSC) blocker [4]. TTX have been used for anaesthetic agents [5], reducing opioid withdrawal symptoms [6], preventing ischemia in post stroke patients [7]. Recent studies also show that TTX has anti-metastatic [8] and anti tumor properties [9].…”
mentioning
confidence: 99%